In vitro culture of zygotic embryos of Butia eriospatha Cultivo in vitro de embriões zigóticos de Butia eriospatha - Diego Pascoal Golle (Semina: Ciências Agrárias, 2013)
The economic use of Butia eriospatha is justified by its potential but is limited by its slow germination. The in vitro culture of zygotic embryos can solve this problem as well as contribute to the conservation and to insert this species in the productive context. The objectives of this study were to evaluate the procedures for surface disinfestation, the effect of gibberellic acid (GA3) on in vitro germination, and the effect of 3 culture media on the increase in fresh mass of zygotic embryos of Butia eriospatha. In the first assay, disinfestation was tested by immersing only the seeds, by immersing the seeds followed by isolation of the embryos, and by immersing only the embryos in sodium hypochlorite (NaOCl). After 30 days of in vitro culture, microorganism contamination was evaluated. In the second assay, in vitro germination was tested using different concentrations (0, 2, 4, 6, and 8 mg·L-1) of GA3. In the third assay, 3 culture media (Murashige and Skoog [MS], woody plant medium [WPM], and Y3) were evaluated. Soaking embryos in NaOCl, with or without seed immersion, produced satisfactory control of microorganisms, unlike the disinfestations tests conducted only on the seed, which were not efficient. In vitro germination of embryos increased with the GA3 concentration. Embryos cultured in Y3 and MS culture media showed a higher increase in fresh mass than those cultured in WPM. To control microorganisms, disinfestation consisted of immersing the seed in 2% NaOCl for 15 min followed by immersing the embryo directly in 1% NaOCl for 10 min. A GA3 concentration of 8 mg·L-1 was required to optimize the germination. After 4 weeks of the in vitro culture, 80% of the embryos germinated. Thus, the use of MS or Y3 culture media is recommended to promote the in vitro growth of Butia eriospatha zygotic embryos. A exploração econômica do butiazeiro (Butia eriospatha) é justificada por suas potencialidades, porém apresenta uma germinação lenta, problema que o cultivo in vitro de embriões zigóticos pode eliminar, além de poder contribuir para a sua conservação e para inserir a espécie no contexto produtivo. Os objetivos foram avaliar metodologias de desinfestação superficial, o efeito do Ácido Giberélico (GA3) sobre a germinação in vitro e do meio de cultura sobre o ganho de massa fresca de embriões zigóticos de Butia eriospatha. No primeiro ensaio foram aplicadas metodologias de desinfestação que incluíram imersão apenas das sementes, ou das sementes e, depois, dos embriões isolados ou, ainda, apenas dos embriões em hipoclorito de sódio (NaOCl), sendo avaliada, após 30 dias de cultivo in vitro, a contaminação por microrganismos. No segundo ensaio, diferentes concentrações (0, 2, 4, 6 e 8 mg·L-1) de GA3 foram testadas em relação à germinação in vitro. Três meios de cultura (MS, WMP e Y3) foram avaliados no terceiro ensaio. A imersão dos embriões em NaOCl associada ou não à imersão das sementes promoveu um controle satisfatório dos microrganismos; ao contrário, desinfestações efetuadas apenas nas sementes não foram eficientes. A germinação dos embriões aumentou com a concentração de GA3. Embriões cultivados nos meios de cultura Y3 e MS apresentaram maiores ganhos de massa fresca que aqueles cultivados em WPM. Para efetuar o controle de microrganismos deve-se realizar a desinfestação em NaOCl a 1% por 10 minutos, diretamente no embrião, após a imersão da semente a 2% durante 15 minutos. A concentração 8 mg·L-1 de GA3 é necessária para otimizar a germinação in vitro de Butia eriospatha, sendo obtidos 80% de germinação após quatro semanas de cultivo. Recomenda-se o emprego dos meios de cultura MS ou Y3 para promover o crescimento in vitro de embriões zigóticos de Butia eriospatha.